Komunikasi Lintas Budaya dalam Menjaga toleransi umat beragama di Kelurahan Sesi Kera Hilir II Kecamatan Medan Perjuangan Kota Medan - Mhd Alpin Azhari Lubis; Iskandar Mubin Dongoran; Irfan Syahputra; M. Joharis Lubis (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Indonesia is a country that is famous for its diversity of tribes, ethnicities, races, cultures, and religions. Our society is a multicultural society, besides that the Indonesian people are also known as a religious nation. In Indonesia alone, there are at least six nationally recognized religions, namely Christianity, Islam, Hindu Catholicism, Buddhism, and Confucianism. With so many religions in Indonesia, people must have an attitude of tolerance towards fellow religious people. Tolerance is a human attitude to respect the differences that exist, both between individuals and groups. Tolerance is a way of respecting and accepting differences in behavior, culture, religion and race that exist and this world. Tolerance is very important to be fostered both within the community and in other spheres. The attitude of tolerance in religious communities can create an atmosphere of peace, tolerance and mutual respect so that they can live side by side without any sense of difference to others. This study aims to examine how cross-cultural communication in maintaining religious tolerance in Sei Kera Hilir II Village, Medan Perjuangan District, Medan City. So that with this study, it can further foster a sense of tolerance between religious communities in the hearts of everyone who reads this journal, thus making them more respectful of one another, not cornering each other, and respecting the opinions of others, and so on.